Combining monoamine oxidase B and semicarbazide-sensitive amine oxidase enzyme inhibition to address inflammatory disease. (15th October 2022) - Foot, Jonathan S.; Buson, Alberto; Deodhar, Mandar; Findlay, Alison D.; Robertson, Alan D.; Turner, Craig I.; Yow, Tin; Zhou, Wenbin; Jarolimek, Wolfgang
Graphical abstract: The discovery of a dual MAO-B/SSAO inhibitor PXS-5131 is reported. The compound offers a compact and rigid three-dimensional structure with superior selectivity over MAO-A. Potency and selectivity are linked to both the double bond geometry and stereochemistry of the allylamine moiety, highlighting the importance of optimal set up of these features in the class of amine oxidase inhibitors. PXS-5131 possesses an attractive preclinical pharmacokinetic profile and has anti-inflammatory properties in models of acute inflammation and neuroinflammation. Abstract: The discovery of a dual MAO-B/SSAO inhibitor PXS-5131 is reported. The compound offers a compact and rigid three-dimensional structure with superior selectivity over MAO-A. Potency and selectivity are linked to both the double bond geometry and stereochemistry of the allylamine moiety, highlighting the importance of optimal set up of these features in the class of amine oxidase inhibitors. PXS-5131 possesses an attractive preclinical pharmacokinetic profile and has anti-inflammatory properties in models of acute inflammation and neuroinflammation.